Broadband omnidirectional anti-reflection property of V-groove textured silicon. (15th November 2019) - Zhao, Yan; Liu, Yaoping; Chen, Quansheng; Chen, Wei; Wu, Juntao; Wang, Yan; Du, Xiaolong
Highlights: V-groove textured silicon was obtained through copper-assisted chemical etching. Anti-reflection performance of V-groove textured silicon was investigated through simulations and experiments. V-groove textured silicon exhibited excellent omnidirectional anti-reflection property. Considering the impact of incident angle, average reflectance of V-groove textured silicon was 9.25%. Abstract: Omnidirectional silicon solar cells with an outstanding anti-reflection property over a broad angular range of incident light show great potential for application in the photovoltaic industry. Many studies have been carried out to investigate the omnidirectional anti-reflection properties of different silicon textured structures. However, the omnidirectional anti-reflection property of the V-groove textured silicon has not been reported, even though the V-groove structure is also one of most frequently used anti-reflective structures for silicon solar cells. In this research, ray tracing simulation is utilized to analyze and validate the omnidirectionality of a micron-sized silicon V-groove structure. In addition, in consideration of the previous complicated fabrication methods of V-groove structure, a brand new fabrication method for the V-groove texturization onto diamond-wire-sawn monocrystalline silicon wafers through copper-assisted chemical etching is presented. Consistent with the simulations, the experimental results similarly indicate that the V-groove textured silicon not only possesses light absorption ability that is comparable to the common random pyramid structure but also exhibits an unexpected excellent omnidirectional anti-reflection property over a wide range of incident angles, demonstrating the great potential for the fabrication of omnidirectional silicon solar cells.